The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/978-3-030-30508-6_44
|View full text |Cite
|
Sign up to set email alerts
|

Generative Adversarial Networks for Operational Scenario Planning of Renewable Energy Farms: A Study on Wind and Photovoltaic

Abstract: For the integration of renewable energy sources, power grid operators need realistic information about the effects of energy production and consumption to assess grid stability. Recently, research in scenario planning benefits from utilizing generative adversarial networks (GANs) as generative models for operational scenario planning. In these scenarios, operators examine temporal as well as spatial influences of different energy sources on the grid. The analysis of how renewable energy resources affect the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…There are multiple works that propose different versions of the different DGMs reviewed above for energy scenario generation. Applications of GANs and WGANs include wind power generation [17], [19], PV power generation [16], [18], [20]- [22], and residential loads [25]. VAEs were applied to learn the distributions of PV and wind power generation [15], concentrated solar power [23], and electric vehicle power demand [24].…”
Section: Dgm-based Scenario Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple works that propose different versions of the different DGMs reviewed above for energy scenario generation. Applications of GANs and WGANs include wind power generation [17], [19], PV power generation [16], [18], [20]- [22], and residential loads [25]. VAEs were applied to learn the distributions of PV and wind power generation [15], concentrated solar power [23], and electric vehicle power demand [24].…”
Section: Dgm-based Scenario Generationmentioning
confidence: 99%
“…A popular modification of GANs are so-called Wasserstein GANs (WGANs), i.e., to use Wasserstein loss functions [14]. Applications of VAEs and (W)GANs include learning distributions of PV and wind power generation [15]- [22], concentrated solar power generation [23], electric vehicle power demand [24], and residential load [25].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature on energy scenario generation, most authors evaluate the PDF on a linear scale (Gu et al, 2019;Jiang et al, 2018Jiang et al, , 2019Schreiber et al, 2019;Wang et al, 2018;Zhang et al, 2020;Wei et al, 2019;Qi et al, 2020;Pan et al, 2019;Zhanga et al, 2018) or the integral over the PDF, i.e., the cumulative distribution function (CDF) (Chen et al, 2018b;Jiang et al, 2019). However, the linear scaled PDF and the CDF can only show differences between historical and generated scenarios for values of high likelihood.…”
Section: Probability Density Functionmentioning
confidence: 99%
“…A popular modification of GANs are so-called Wasserstein GANs (WGANs), i.e., to use Wasserstein loss functions (Arjovsky et al, 2017). Applications of VAEs and (W)GANs include learning distributions of PV and wind power generation (Zhanga et al, 2018;Chen et al, 2018b;Jiang et al, 2018;Wei et al, 2019;Zhang et al, 2020;Chen et al, 2018a;Jiang et al, 2019;Schreiber et al, 2019), concentrated solar power generation (Qi et al, 2020), electric vehicle power demand (Pan et al, 2019), and residential load (Gu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the generation of wind and PV scenarios, GAN-based scenario generation was also applied to residential load forecasts (Gu et al, 2019) and hydrowind-solar hybrid systems (Wei et al, 2019). Schreiber et al (2019) study different loss functions for GANs and found the Wasserstein distance to be superior to the binary-cross-entropy. Besides GANs, a popular type of DGMs are variational autoencoders (VAEs) (Kingma and Welling, 2014).…”
Section: Introductionmentioning
confidence: 99%